TPS-Flipgrid: Transforming EFL speaking class in the 21st century - Budiarta, I Komang; Santosa, Made Hery (English Review: Journal of English Education, 2020)
Innovative teaching model in the 21st century is of necessity because in this digital transformation era, lecturers deal with tech-savvy students. These students should be taught differently; it can be done by integrating teaching technique with newly-updated and technological-based media or platform. In English Education Study Program, the lecturer still made use of conventional technique and it was monotonous and uninteresting. The present qualitative research with case study design was mainly intended to fathom out the students’ perceptions and the benefits of implementing TPS-Flipgrid in EFL speaking class. The implementation of TPS-Flipgrid in the present qualitative research with case study design for the sake innovating EFL speaking class has brought the language learning into certain level. The research clearly figured out that the perception of the third semester students was positive. They thought that TPS-Flipgrid was an innovative and flexible teaching model; besides, this model could invite active involvement and equalize classroom and online face-to-face interaction. The teaching model has successfully improved the students’ speaking performances and their 21st century life skills such as collaboration, creativity, communication, and critical thinking. Considering the significant results of applying TPS-Flipgrid, the implementation of this teaching model should be continuously carried out and improved